Can man ever be rich? - Omer, Spahic (islamicity.org, 2019)
Once while describing an aspect of man’s fundamental nature, Prophet Muhammad (pbuh) said that the son of Adam becomes old with senility, but yet two things remain with him intact: greed and hope (Sahih al-Bukhari). The Prophet (pbuh) also taught that when the latter two become unrestrained, taking over a person’s total being, he with his actions and decision making, in turn, becomes uncontrollable. He stops at nothing in order to try to satisfy his raging impulses. No action, or word, that comes from such a person should be seen as a surprise. The Prophet (pbuh) thus said that if the son of Adam possessed two valleys of gold, he would long for a third one; “and nothing would fill (satiate) the stomach – or the mouth -- of the son of Adam but dust (that is, after he dies)” (Sahih Muslim). Man can easily become a world of paradoxes. Under the pressure of his recurring misjudgments, his inborn disposition and a myriad of external factors and forces, man can easily give in to the advances of his perennial anxieties, unfounded optimism and profligacy, relegating the transcendent power of his reason (intellect or ‘aql), as well as his primordial nature (instinct or fitrah), to the backseat. One moment he can think and act like an angel; the next he can be like a devil. The similar thing Satan (Iblis) had in mind when he plotted to deceive Adam and his wife Eve (Hawa) and drive them out from the Garden of Eden. He whispered to them, coaxing them: “Shall I lead you to the Tree of Eternity and to a kingdom that never decays?” (Ta Ha, 120).